Barriers in use of colostrum, Breast milk, and supplemental feed: assessing maternal Knowledge & practices - Hina Jawaid; Marriam Sheraz; Khudija Amna Arif; Zia Ul Hassan; Akhter, Hina (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Colostrum and breast milk are not only highly nutritious but also a source of maternal antibodies for infants. We explore maternal awareness and barriers in use of colostrum and breast milk. METHODOLOGY: This cross-sectional study included mothers of children aged 3 years or less who visited primary care centers in urban and peri-urban areas of Lahore, Pakistan, between December 2020 to March 2021. RESULTS: A total of 384 mothers were included in the study, mean age was 28 years. 47% (n=179) had primary or secondary school education. Higher maternal education (p=0.05) and age were associated with better knowledge about the benefits of colostrum. Reasons for not giving colostrum among mothers without formal education (42%) were “it’s not clean milk”, while 38% of mothers with higher education give a reason they could not feed because find it difficult due to C-section. Use of supplemental feed was noted across all educational levels, 60% mothers with no educational background preferred bovine milk, whereas 79% of highly qualified ones preferred formula milk (p=0.00). The use of formula milk was more frequently observed in families with 100,000 PKR per month and above (p=0.00). 80% of mothers were unaware that bovine milk in infants can lead to anemia. CONCLUSION: There is inadequate knowledge, among mothers of all educational levels with reference to colostrum use and the relationship between consumption of bovine milk by infants and iron deficiency. Measures to improving maternal nutritional awareness and optimize infant feeding practices during antenatal visits are needed.